2010
DOI: 10.1093/eurpub/ckq002
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Croatian pupils' unhealthy behaviours and health outcomes: role of school, peers and family affluence

Abstract: Compared to socioeconomic inequalities, greater inequalities in unhealthy behaviours were connected to school environment and peer group, and in health outcomes to school environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 30 publications
0
22
1
2
Order By: Relevance
“…The findings of previous studies [ 19 , 33 ] were also confirmed on comparing high- and low-income families, in that the latter were associated with higher odds of poor self-reported health and life dissatisfaction. In contrast with previous reports [ 24 , 34 ], however, our findings did not reveal an apparent socioeconomic gradient in multiple health complaints. From our study, it emerged that boys enjoyed a considerable advantage over girls in terms of health status, which confirms the results reported in the literature [ 26 , 35 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of previous studies [ 19 , 33 ] were also confirmed on comparing high- and low-income families, in that the latter were associated with higher odds of poor self-reported health and life dissatisfaction. In contrast with previous reports [ 24 , 34 ], however, our findings did not reveal an apparent socioeconomic gradient in multiple health complaints. From our study, it emerged that boys enjoyed a considerable advantage over girls in terms of health status, which confirms the results reported in the literature [ 26 , 35 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Respondents were regarded as suffering from multiple health complaints if they reported experiencing two or more symptoms “more than once a week” or “about every day” [ 24 ]. Respondents were assessed for eight symptoms on a five-point scale: difficulty in falling asleep, headache, feeling dizzy, stomach-ache, backache, depression, irritability or bad temper, and nervousness [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…It could be that the school achievement is more important for gymnasium school pupils than it is for those in industrial or crafts and technical or related schools, therefore contributing to lower KIDSCREEN-10 scores. Some authors also report that a poor school environment increases the odds of lower self-rated health, multiple health complaints, and lower life satisfaction [54]. Thus, better KIDSCREEN-10 (higher) and SDQ scores (lower) might have an underlying dimension connected to the school environment.…”
Section: Discussionmentioning
confidence: 99%
“…This measure has been found to be associated with health behaviours and risk taking among adolescents, [ 35 , 36 ]. Due to the design of the response alternatives, as well as suggested in other research [ 37 ], the answers were recoded into fair/poor vs. good/excellent.…”
Section: Methodsmentioning
confidence: 99%